DESIGN OF CONCRETE RETAINING WALL WITH BORED PILE REINFORCEMENT FOR LANDSLIDE MANAGEMENT - Arbianto, Reki; Kartawidjaya, Maria A; Mulyadi, Melisa (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2022)
Abstract.Â Road is one of the transportation infrastructure that plays an important role in supporting regional development, increasing the regional economy, facilitating the mobility of people, goods and services. For this reason, in order to support national economic activities, the Ministry of Public Works and Public Housing through the Directorate General of Highways carries out the planning and construction of several new roads on an ongoing basis. In addition, for existing roads, the Directorate General of Highways needs to carry out maintenance so that existing assets can continue to function. The threat of natural disasters and the instability of road bodies is a serious problem. This can cause damage to the road body and even the road body can be cut off suddenly, resulting in reduced road performance. One of the roads in Maybrat district, precisely in the Ayawasi â€“ Sisu KM 273+500 section, experienced a road collapse that cut off access between districts, resulting in a stagnation of economic activity. Therefore, a landslide handling design is needed so that the road can be accessed again.The design process was carried out through several stages, including Preliminary Survey, Hydrological Survey, Geotechnical and Geological Survey, Topographic Survey, and Planning. In the planning process, the most effective and efficient design will be selected according to field conditions. Slope stability analysis using Slope/W software. Based on the results of the planning, the design of the Concrete Soil Retaining Wall with bored pile reinforcement is used as an alternative treatment because it can be done easily in the field and can overcome the problem of landslides in the area.Keywords: Safety factor; Concrete Retaining Wall; Bored Pile; Landslide; Slope-W